KRITIK HADIS DALAM PENDEKATAN FILOSOFIS - Taufiqurrahman Taufiqurrahman (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The research or criticism of hadith is always directed at the criticism of sanad (external criticism; naqd al-khariji) and matan criticism (internal criticism; naqd al-dakhili). In the criticism of sanad (naqd al-khariji) the focus of the study is always directed at the quality of the narrators and the method of transmission used; whether the credibility of the narrators and the hadith is acknowledged and whether the traditions of tahammul and there 'indicate that he is a hadith of the Prophet. Whereas in the criticism of matan (naqd al-dakhili) it is more directed at the provisions that matan hadith must not conflict with the Koran; Mutawatir traditions or those of higher quality; historical facts; common sense; the five senses; and avoid syadz and ‘illah.Departing from the focus of the study of criticism of Sanad on the assessment of the quality of the narrators, the existence of the Science of Jarh wa Ta'dil is absolutely necessary. It is through this knowledge that the judgment of the critical scholars against the narrators is revealed by jarh or ta'dil or from the point of view of whether or not their transmission is accepted.